A study on building management concern in providing access and facilities for person with disabilities (PWD) in Klang Valley Shopping Malls / Nur Ezzatul Edhlin Aziz Jaafar - Aziz Jaafar, Nur Ezzatul Edhlin (Faculty Architecture, Planninng and Surveying, 2015)
Generally, this study concerned about the access and facilities for person with disabilities (PWD) in shopping malls. It related to the building management concern in providing access and facilities for PWD in Klang Valley shopping malls. As this study aimed is at assessing building management concern in providing access and facilities for PWD in Klang Valley shopping malls, it has three objectives that need to be achieved. Firstly to identify related provisions of access and facilities for PWD in shopping malls, secondly to examine building management awareness, willingness, and readiness in providing access and facilities for PWD in shopping malls and last one is to recommend measures to increase building management awareness, willingness, and readiness in providing access and facilities for PWD in shopping malls. Ten shopping malls in Klang Valley were selected based on the capacity of customer visits which is that frequented by visitors including PWD. The research methodology that has been implemented during the research is through the visual observation about the access and facilities for PWD that has been provided in shopping malls and the structured interview has been conducted to obtain the information about the awareness, willingness, and readiness of building management in providing access and facilities for PWD in shopping malls and to fulfill the objectives. The data is obtained from the survey that has been carried out at the selected shopping malls or building management. All the data has been gathered and analyzed, and have been presented or shows into forms of table and charts. Findings show that the score among of respondents level of awareness, willingness and readiness in providing access and facilities for PWD in shopping malls selected in Klang Valley. The level of awareness is higher compare to the level of willingness and readiness. Most of the respondents and their building management have excellent awareness and willingness and good readiness in providing access and facilities for PWD in shopping malls. Recommendations are made to increase building management awareness, willingness, and readiness in providing access and facilities for PWD in shopping malls.